Public policies and local experiences of landscape tourism : the example of Pantanal - Carla Moura de Paulo; Neli Aparecida de Mello-Théry (Via@)
This article analyses public policies and local experiences of tourism in Brazilian Pantanal through environmental approach using geographical categories of analysis. It is structured on four items that address tourism policy, its organization and governance, its relations with environmental policy represented by territories of environmental conservation, analysing the role of these Pantanal policies in multiple scales. To analyse the roles undertaken by Pantanal policies on Pantanal complex it became necessary to give some elements that characterizes it. Thus, considering tourism policy in its territorial aspect, our objective is to highlight relations between transformations in Pantanal region as it turned itself into a tourist destination and actions of public policies in their multiple administrative scales that can influence the process.